2019
DOI: 10.1051/0004-6361/201935147
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition in quiescent prominences

Abstract: Context. The first ionization potential (FIP) bias is currently used to trace the propagation of solar features ejected by the wind and solar eruptions (coronal mass ejections). The FIP bias also helps us to understand the formation of prominences, as it is a tracer for the solar origin of prominence plasma. Aims. This work aims to provide elemental composition and FIP bias in quiescent solar prominences. This is key information to link these features to remnants of solar eruptions measured in-situ within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…The dominantly photospheric plasma composition of the erupting sigmoid/flux rope is in agreement with the photospheric origin material in erupting (e.g. Widing et al 1986;Feldman 1992;Spicer et al 1998) and quiescent prominences/filaments (Parenti et al 2019).…”
Section: Local Evolution -Flux Ropesupporting
confidence: 80%
See 1 more Smart Citation
“…The dominantly photospheric plasma composition of the erupting sigmoid/flux rope is in agreement with the photospheric origin material in erupting (e.g. Widing et al 1986;Feldman 1992;Spicer et al 1998) and quiescent prominences/filaments (Parenti et al 2019).…”
Section: Local Evolution -Flux Ropesupporting
confidence: 80%
“…Feldman 1992;Spicer et al 1998;Ciaravella et al 2000). Parenti et al (2019) confirmed that quiescent prominences also have photospheric composition.…”
Section: Introductionmentioning
confidence: 63%
“…Another environment to which this work may extend is that of prominences. These regions of cooler, higher density plasma in the TR and corona are shown in the recent work of Parenti et al (2019) to have similar pressure to that which is used in the modelling here. The structures are relatively low in the atmosphere, and so the radiation field will be diluted by a similar amount as here.…”
Section: Discussionsupporting
confidence: 53%
“…Prominences and filaments can be fairly stable regions. These quiescent structures retain photospheric composition according to Parenti et al (2019). Quiescent filaments, that may exist at all latitudes, at solar minimum are preferentially located at high latitudes, 45 • -50 • , and often form a crown around the polar caps.…”
Section: Coronal Streamers During the Solar Cyclementioning
confidence: 99%